Improvement measures and prospects for the development of “Glyfada Marina”, Attica, Greece - Alamanis, Ν; Drimonas, Ch; Milozis, E; Lazogiannis,Κ; Papageorgiou, G.; Vassilakis, Ε; Alexopoulos, J.; Kotsopoulos, S; Chouliaras,Ι (1st International Scientific Conference on Design and Management of Port Coastal and Offshore Works, 2019)
For several years, Greece has set as a priority the strengthening of maritime tourism, such as the tourism of yachts for which tourist marinas have been created. The most important marinas of the country include the “Glyfada Marina”, whose works began on the coastal front after 1960, thus changing the area’s shape and planning. The main objective of the present work is to investigate the improvement measures and prospects for the development of the “Glyfada Marina” consisting of four basins, being one of the most beautiful and developed marinas in the country since it is an important attraction for tourist yachts. For this reason, on-site visits to the port area were carried out, both on the sea and on the coastal part of the coastal zone, in order to record the current situation, so as to reach as accurately as possible the characteristics and the range of the internal port works and facilities of the aforementioned tourist port. Furthermore, any deficiencies or failures that need improvement are presented, labeled and classified in order to continue unhindered activities in the marina area. Finally, improvement and upgrading measures are proposed that can contribute positively to the tourist and economic development of the port and the municipality of Glyfada in general.